Planning, Allocative and Administrative Efficiency of School Facilities Management as Correlates of Academic Performance of Senior Secondary School Students in Adamawa State, Nigeria - T. Takwate, Kwaji (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This study investigated the planning, allocative and administrative efficiency of school facilities as correlates of academic performance of Senior Secondary School (SSS) students in Adamawa State, Nigeria. Correlational research design was adopted for the study. A sample of 153 school principals, 377 teachers and 19 staff of Adamawa State Ministry of Education Planning Division was randomly drawn from 248 SSS principals and 6,450 teachers using Proportionate sampling technique from five education zones of Adamawa State.School Facilities Planning and Allocation Questionnaire (SFPAQ) and Management of School Facilities Questionnaire (MSFQ), Students’ Academic Performance Proforma and Checklist were used for data collection. The reliability coefficients for SFPAQ and MSFQ were 0.82 and 0.74 respectively using Cronbach alpha. Four research questions and three null hypotheses were answered and tested at 0.05 levels of significance using mean, standard deviation and Pearson Product Moment Correlation Coefficient. From the analysis, the study revealed efficient level of school facilities planning in Adamawa State, while level of school facilities allocative and administration efficiency were not efficient. The level of students’ academic performance in WAEC/SSCE May/June 2013 – 2015 was found to be poor. The study equally revealed a significant relationship between school facilities planning efficiency, allocative efficiency, administrative efficiency and students’ academic performance in Adamawa State, Nigeria. The study recommended that adequate equipping of all Senior SSS in the State should be done using appropriate and efficient procedures for allocation by government, and school principals should frequently carry out comprehensive assessment of facilities in their schools to determine areas of need.